2014
DOI: 10.3844/ajassp.2014.216.222
|View full text |Cite
|
Sign up to set email alerts
|

CLIENTS’ SATISFACTION WITH REFERRAL SYSTEM IN KARBALA

Abstract: Referral is a dynamic process and it had been recognized as crucial since the Alma Ata declaration in 1978. Hospitals are overcrowded with patients who could be more cheaply treated in smaller facilities is a common feature of poorly functioning Referral System (RS). Client Satisfaction (CS) is an important parameter in the assessment of health care quality. A descriptive cross sectional study conducted to measure CS with RS in Karbala province in Iraq. A special questionnaire based on 5 points Likert scale pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 28 publications
(24 reference statements)
2
11
3
Order By: Relevance
“…Patients in the lower income categories perceived they had better access to medical care than patients in the highest income category. The relationships between the sociodemographic characteristics of patients and their different dimensions of satisfaction may help healthcare providers to meet the different needs of patients based on their gender, age and socio-economic status (Abutiheen, 2014;Mercer et al, 2008;Lin et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Patients in the lower income categories perceived they had better access to medical care than patients in the highest income category. The relationships between the sociodemographic characteristics of patients and their different dimensions of satisfaction may help healthcare providers to meet the different needs of patients based on their gender, age and socio-economic status (Abutiheen, 2014;Mercer et al, 2008;Lin et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…But there was no association between the other socio-demographic factors and referral satisfaction. 4 A similar study done in Nigeria also showed that 53.2% of patients were satisfied with the referral process of primary care. 5 Difficulty in obtaining referral request, delayed response, getting approval was time-consuming and difficult, and the hospital did not communicate with referred health facility on time were the possible reasons described for the dissatisfaction.…”
Section: Introductionmentioning
confidence: 72%
“…This result is lower as compared to the study done in Nigeria (52.3%), 5 and Iraq (67%). 4 The possible reason for the difference could be the difference in the availability of essential resources, both human (staff number and skill to manage the referral), and physical (infrastructure, transport), and as well as communication and coordination of the referring and receiving health facilities. The overall satisfaction rate toward referral was consistent with studies conducted in other services such as inpatient service satisfaction 46.2%, 12 which is higher than studies done in the outpatient service satisfaction 27.8%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The holy city is attended by tens of million visitors each year, and several big mass gathering visits including the Arbaeen visit, which represents the biggest annual mass gathering in the world occur in Karbala. 16 This study aims to describe CT scans' findings of COVID-19 patients, particularly GGOs, and to estimate the association between these opacities and the time of clinical presentation.…”
Section: Introductionmentioning
confidence: 99%